Therapeutic proteins immunogenicity: a peptide point of view - Feliciana Real-Fernandez; Fosca Errante; Andrea Di Santo; Anna Maria Papini; Paolo Rovero (Exploration of Drug Science)
Protein therapeutics are extensively used in the treatment of autoimmune diseases, but a subset of patients appears to be refractory to these treatments, mainly due to the development of an immune response to the drug. A better understanding of the mechanism underlying the therapeutic drug’s failure becomes fundamental for the development of new and more effective treatments. Unfortunately, there are few cases where the exact mechanisms through which drugs bypass immunological tolerance and provoke immunogenicity have been studied. In this context, peptide epitope identification gained increasing importance in investigating the molecular mechanism of therapeutic drug’s immune responses. Despite peptide identification and use to monitor anti-drug antibody (ADA) profiles is a promising research field, their use is far away from a wide application both at the research and at the commercial level. Herein it is reported a compilation of studies in which peptides are directly involved in anti-drug immune responses, becoming the molecular key step for a better understanding of refractory reactions in therapeutic drugs. An overview on T-cell and B-cell peptide recognition is given, showing the growing potential and advantages of peptides when used in the field of refractoriness to drugs. This review includes studies describing antigenic peptides that enable enhanced ADA detection directly in patients’ sera, as well as the proof of concept that asses the use of peptides instead of proteins, to facilitate the identification of neutralizing ADA.